Development of proton CT imaging system using plastic scintillator and CCD camera. (18th May 2016) - Tanaka, Sodai; Nishio, Teiji; Matsushita, Keiichiro; Tsuneda, Masato; Kabuki, Shigeto; Uesaka, Mitsuru
Abstract: A proton computed tomography (pCT) imaging system was constructed for evaluation of the error of an x-ray CT (xCT)-to-WEL (water-equivalent length) conversion in treatment planning for proton therapy. In this system, the scintillation light integrated along the beam direction is obtained by photography using the CCD camera, which enables fast and easy data acquisition. The light intensity is converted to the range of the proton beam using a light-to-range conversion table made beforehand, and a pCT image is reconstructed. An experiment for demonstration of the pCT system was performed using a 70 MeV proton beam provided by the AVF930 cyclotron at the National Institute of Radiological Sciences. Three-dimensional pCT images were reconstructed from the experimental data. A thin structure of approximately 1 mm was clearly observed, with spatial resolution of pCT images at the same level as that of xCT images. The pCT images of various substances were reconstructed to evaluate the pixel value of pCT images. The image quality was investigated with regard to deterioration including multiple Coulomb scattering.